The public's perceptions toward theme parks as a recreational activity - Fiffy Hanisdah Saikim; Nor Akmar Abdul Aziz; Siti Nisrina Mohd Radi; Thivya Laxshmy Raman; Norhuda Salleh; Nordiana Mohd Nordin (Global Academic Excellence, 2023)
A theme park is an attraction that the public enjoys. A theme park provides amusement and creates a leisure time for the public to spend time with family, friends and other relatives. Therefore, it is critical to determine the public's expectations and perceptions of theme park recreation. The purpose of this study is to determine the level of public participation in a theme park recreational activity. The theme parks selected are Sunway Lagoon Water Park, iCity Water World, and Wet World Water Park. All of the selected theme parks are located in the state of Selangor. The objective of the study is to investigate the influence factor of public perception on theme park attendance based on social demographics. Due to the Covid-19 situation, the survey was conducted through an online form using a Google form. A total of 437 people from the selected theme parks were surveyed. The study found that most theme park visitors are students and are between 18 and 30 years old. The result shows that public participation in theme park recreational activities is significant. It was found that people who do their leisure activities in amusement parks have higher expectations. On the other hand, the influence factor of public perception of participation in theme park leisure activities was significant. The iCity Water World has the highest influence. The influence factor of public perception of participation is statistically significant in theme parks. Nevertheless, the management should cooperate and communicate with the government and private organizations to improve the country's economy due to the Covid-19 situation.